Improving Learning Outcomes of Tahsin Al-Quran using MyQuran-Mobile Application at Junior High School Al-Irsyad Surakarta - Salsabilla, Alfina; Nurrohim, Ahmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This study aims to explore the use of colored Quran in learning tahsin tajweed at Junior High School Al-Irsyad Surakarta using the MyQuran-Mobile application. The Classroom Action Research Method (PTK) with two cycles was carried out involving 30 students. The results showed a significant improvement in the understanding of tahsin tajweed rules in the group that used colored Qurans. Teachers and students show increased activity, motivation, and learning outcomes. Qualitative data are obtained from observations of teacher and student actions, while quantitative data from students' Quran Tahsin test. The use of colored Quran facilitates comprehension, teaching, and improves memorization, as well as helping students understand the rules of tajweed better. Thus, it can be concluded that the use of colored Quran is effective in improving students' Quran reading skills, as well as creating a supportive and motivational learning environment for the development of Quran reading skills.